Study of correlation between optical flux and polarization variations in BL Lac objects. Issue 3 (16th September 2022) - Rajput, Bhoomika; Pandey, Ashwani; Stalin, C S; Mathew, Blesson
ABSTRACT: Polarized radiation from blazars is one key piece of evidence for synchrotron radiation at low energy, which also shows variations. We present here our results on the correlation analysis between optical flux and polarization degree (PD) variations in a sample of 11 BL Lac objects using ∼10 yr of data from the Steward Observatory. We carried out the analysis on long-term (∼several months) as well as on short-term time-scales (∼several days). On long-term time-scales, for about 85 per cent of the observing cycles, we found no correlation between optical flux and PD. On short-term time-scales, we found a total of 58 epochs with a significant correlation between optical flux and PD, where both positive and negative correlation were observed. In addition, we also found a significant correlation between optical flux and γ -ray flux variations on long-term time-scales in 11 per cent of the observing cycles. The observed PD variations in our study cannot be explained by changes in the power-law spectral index of the relativistic electrons in the jets. The shock-in-jet scenario is favoured for the correlation between optical flux and PD, whereas the anticorrelation can be explained by the presence of multizone emission regions. The varying correlated behaviour can also be explained by the enhanced optical flux caused by the newly developed radio knots in the jets and their magnetic field alignment with the large-scale jet magnetic field.